Legal Challenges and Reforms in Dutch Labor Law Insights from Rotterdam - Maarten Bakker; Jan de Vries; Tom de Boer (CV. Tirta Pustaka Press, 2026)
This study examines the legal challenges and reforms in Dutch labor law, with a particular focus on Rotterdam, a major urban and economic center. It critically analyzes recent legislative changes, especially the Balanced Labour Market Act, which aims to improve employment security and reduce disparities between temporary and permanent contracts. The research highlights persistent issues affecting non-standard, gig, and migrant workers, including gaps in social protection, legal classification, and collective representation. Using a qualitative approach that combines doctrinal analysis, case studies, and examination of labor market practices, the study identifies both the successes and limitations of current reforms. Findings indicate that while legislative measures have enhanced worker security and fairness for certain groups, significant vulnerabilities remain for platform-based and flexible workers. The study concludes that labor law must adopt adaptive, inclusive, and evidence-based strategies to respond effectively to technological, economic, and social transformations in Rotterdam’s labor market. Recommendations include clarifying employment definitions, extending protections to non-standard workers, strengthening migrant labor safeguards, and developing innovative models of collective representation. The insights from Rotterdam provide broader implications for understanding the interaction between labor law, employment practices, and social justice in modern urban economies.